How science works - Harvey, Derek; Jackson, Tom 1972-; Smith, Ginny; Sturgeon, Alison; Woodward, John 1954- (Dorling Kindersley Limited, 2018)
Answering all your burning scientific questions, from what it means to be alive to why things explode, How Science Works explains science facts throughout amazing diagrams and infographics. Unlock the secrets of the universe, such as whether a robot takeover is possible, and marvel at the surprising simplicity of gravity.Dazzle your friends and family with answers to their everyday science questions such as; why do sirens change pitch as they pass by? How do planes stay in the air? Plus many more!Learn how to explain the mind-boggling concepts that eluded you at school, all the way through to more recent fascinating topics such as the discovery of the Higgs Boson- this really is science made simple.